2010
DOI: 10.1016/j.jnutbio.2009.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Differential response to zinc-induced apoptosis in benign prostate hyperplasia and prostate cancer cells☆

Abstract: Zinc concentrations in the prostate are uniquely high but are dramatically decreased with prostate cancer. Studies have suggested that increasing zinc in the prostate may be a potential therapeutic strategy. The goal of this study was to evaluate the antiproliferative effects of zinc in prostate cancer cells (PC-3) and noncancerous benign prostate hyperplasia (BPH) cells (BPH-1) and to define possible mechanisms. PC-3 and BPH-1 cells were treated with zinc (0–250 μM) for 24 and 48 h, and cell growth and viabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 44 publications
0
26
0
Order By: Relevance
“…It was found that patients with diets rich in zinc exhibited reduced PCA mortality especially in patients with localized tumors [124]. Perhaps relatedly, exogenous zinc more potently inhibited the proliferation of benign prostatic hyperplasia cells (BPH-1) as compared to PC3 cells [125]. …”
Section: Prostate Cancer Chemopreventive Agentsmentioning
confidence: 99%
“…It was found that patients with diets rich in zinc exhibited reduced PCA mortality especially in patients with localized tumors [124]. Perhaps relatedly, exogenous zinc more potently inhibited the proliferation of benign prostatic hyperplasia cells (BPH-1) as compared to PC3 cells [125]. …”
Section: Prostate Cancer Chemopreventive Agentsmentioning
confidence: 99%
“… 13 Furthermore, the role of zinc in the development and progression of prostate cancer and its widespread antitumor efficacy have been shown in several malignancies. 14 17 Intracellular zinc status is associated with prostate carcinogenesis. For example, zinc deficiency contributes to tumor progression and development in cultured HRPC cells, 18 whereas increased levels of intracellular zinc decrease cancer cell proliferation and induce apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…4, 7 In fact, the concentration of fetal bovine serum (FBS) in the culture medium is an important factor affecting the zinc concentration to induce apoptosis, which is demonstrated to range from 15  μ M in the medium without FBS to 150  μ M in the medium with 10% FBS supplements. 38, 39, 40 Using the regular cell culture condition with 10% FBS, we observed that moderate zinc concentration (150  μ M) induces significant apoptosis by promoting p21 WAF1/Cip1 expression in both LNCaP and PC3 cells. Moreover, zinc-induced cell apoptosis or p21 WAF1/Cip1 augment were blocked by the chelating agents, which provided the evidence for the link between the reduction of intracellular zinc concentration and the development of prostate cancer.…”
Section: Discussionmentioning
confidence: 93%